Effect of Impact and Bearing Parameters on Bird Strike with Aero-Engine Fan Blades - Bin Wu; Reza Hedayati; Zhehua Li; Mahsa Aghajanpour; Guichang Zhang; Junhong Zhang; Jiewei Lin (Applied Sciences, 2021)
Bird strikes are one of the most dangerous incidents occurring to aircraft engines and can inflict heavy casualties and economic losses. In this study, a smoothed particle hydrodynamics (SPH) mallard bird model has been used to simulate bird impact to rotary aero-engine fan blades. The simulations were performed using the finite element method (FEM) by means of LS-DYNA. The reliability of the material model and numerical method was verified by comparing the numerical results with Wilbeck’s experimental results. The effects of impact and bearing parameters, including bird impact location, bird impact orientation, initial bird velocity, fan rotational speed, stiffness of the bearing, and the damping of the bearing on the bird impact to aero-engine fan blade are studied and discussed. The results show that both the impact location and bird orientation have significant effects on the bird strike results. Bird impact to blade roots is the most dangerous scenario causing the impact force to reach 390 kN. The most dangerous orientation is the case where the bird’s head is tilted 45° horizontally, which leads to huge fan kinetic energy loss as high as 64.73 kJ. The bird’s initial velocity affects blade deformations. The von Mises stress during the bird strike process can reach 1238 MPa for an initial bird velocity of 225 m/s. The fan’s rotational speed and the bearing stiffness affect the rotor stability significantly. The value of bearing damping has little effect on the bird strike process. This paper presents a procedure for evaluating the strength of fan blades against bird strike in the design stage.